Effect of manufacturing errors on load distribution in large diameter slewing bearings of fast breeder reactor rotatable plugs. (May 2016) - Aithal, Sriramachandra; Siva Prasad, N; Shunmugam, MS; Chellapandi, P
Fuel and other subassemblies in fast breeder reactor are handled through a combination of small rotatable plug, large rotatable plug and transfer arm. Rotation of the plugs is facilitated through large slewing bearings. These bearings are subjected to heavy loads and moments. Manufacturing errors on the rolling elements and races influence the load sharing among the elements. As a result, higher load acting on a rolling element causes excessive local deformation and unacceptable indentation. The higher load can also cause excessive sub-surface shear stress and fatigue failure of rolling races. Too stringent tolerances demand sophisticated machines, whereas liberal tolerances mean compromise on the performance and life of the bearing. There are no established methods for design of slewing bearings that include the influence of manufacturing errors. Hence, an attempt has been made to find the influence of manufacturing errors on load distribution among the rolling elements using finite element method. It is observed that size error on the ball and waviness error (waviness spacing and height) on the raceway are the two influencing factors on load distribution. To study the influence of waviness error on the raceway, three sectors of bearing simulating waviness spacing of 10.8°, 18° and 36° with different waviness (peak-to-valley) height of 30 µm, 50 µm and 75 µm are analysed. It is observed that waviness height has larger influence on the load distribution among bearing balls when compared to waviness spacing.